Seed biometry and the effect of pre germinative treatments, temperature, and light on seed germination and subsequent growth of three Stryphnodendron species - Kissmann, Camila [UNESP]; Quintao Scalon, Silvana de Paula (Torrey Botanical Soc, 2011)
KISSMAN, C. (Universidade Estadual Paulista (UNESP), TB, Departamento de Botanica, Pos-Graduacao em Biologia Vegetal. Rio Claro, SP) and S. P. Q. SCALON (Universidade Federal da Grande Dourados (UFGD), Faculdade de Ciencias Agrarias. Dourados, MS). Seed biometry and the effect of pre germinative treatments, temperature, and light on seed germination and subsequent growth of three Stryphnodendron species. J. Torrey Bat. Soc. 138: 123-133. 2011. - This work assesses the seed biometry of Stryphnodendron adstringens. S. obovatum and S. polyphyllum species, the effectiveness of some pre-germination treatments to break physical coat dormancy, and the effects of different temperatures and light qualities on the germination of these seeds. The biometry data show that the seeds of S. polyphyllum are bigger than those of the other two species, whose seed characteristics are very similar. Stryphnodendron adstringens and S. polyphyllum present the highest germination percentage and emergence speed index when their seeds are scarified with sulfuric acid for 40 min and then soaked in GA(3) for 24 h. For S. obovatum, the highest percentage and emergence speed index were reached when seeds were scarified with sulfuric acid for 40 min or scarified with sulfuric acid for 40 min and then soaked in water, but these values did not differ statistically from the other treatments. Seeds of the three evaluated Stryphnodendron species proved insensitive to light. The temperatures used were within the range of optimum temperatures for the species.
Keywords: barbatimao; Brazilian savanna; phytochrome; scarification; sulfuric acid